Pengaruh Sanksi Perpajakan dan Self Assessment System terhadap Persepsi Wajib Pajak Mengenai Penggelapan Pajak (Tax Evasion) - Sundari Sundari (Jurnal Kajian Akuntansi, 2019)
Tax evasion, is an act of illegal tax evasion, tax evasion is done to minimize the amount of tax payable by way of breaking the law and not in accordance with the legislation in force. This research aims to analyze the effect of tax sanctions and self assessment system against taxpayer perceptions about tax evasion in the Office of the tax palayanan pratama Indramayu. Determination of the sample in this research was conducted using the formula slovin, and obtained 100 respondents as samples. The data used is the taxpayer data registered on the KPP Pratama Indramayu in 2017. Data analysis method used in this research is by using multiple linear regression. Before using regression analysis, then performed a classic assumption test first, which includes test normality test, multikolonieritas test, and heteroskedastisitas. Testing in this study performed using SPSS software version 23 for windows. The results of this research show that the sanctions affect taxation taxpayer perceptions about tax evasion, while the self assessment system does not have an effect on the perception of taxpayers about tax evasion.Keywords: Tax sanctions; Self assessment system; Tax Evasion